The Effectiveness of Al-Islam Kemuhammadiyahan Learning Based on Cooperative Learning in Shaping Students' Religious and Democratic Character at SMK Muhammadiyah 3 Karanganyar - Kusumawardani, Intan; Nashir, Muhammad Ja'far; Samsuri, Muh (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This study aims to: 1) Describe the implementation of Al-Islam Kemuhammadiyahan learning in shaping students' religious and democratic character at SMK Muhammadiyah 3 Karanganyar; and 2) Analyze the application of the Cooperative Learning method in strengthening these characters. Using a qualitative descriptive approach, data were collected through observations, interviews, and document analysis to deeply explore the learning process and its impact. Data were then analyzed through data reduction, presentation, and conclusion drawing. The research findings reveal that: 1) The Al-Islam Kemuhammadiyahan learning at SMK Muhammadiyah 3 Karanganyar has not yet fully met the three core competencies—attitude, knowledge, and skills—outlined by the Muhammadiyah Central Leadership's Majelis Dikdasmen; 2) The application of the Cooperative Learning model has proven effective in strengthening students’ religious and democratic character; and 3) This model fosters greater student activeness, encourages collaborative learning, and helps students internalize Islamic teachings and democratic principles in their daily behavior. Through Cooperative Learning, students engage more critically and collaboratively, which not only enhances their understanding of religious concepts but also cultivates democratic attitudes such as tolerance, respect, and responsibility. This research contributes to efforts in improving Al-Islam Kemuhammadiyahan learning practices in Muhammadiyah schools.